CHARACTERISTIC ORGANOLEPTIC LANDRACE PORK RESULTED IMMERSION OF ROBUSTA COFFEE EXTRACT (Coffea canephora) - A. P., Barus; Wibawa, A. A. P. P.; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aimed to study how the different levels of concentrations of robusta coffee powder in improving organoleptic characteristic of landrace pork. This study uses a 1 hour immersion in each treatment with a research design using a Completely Randomized Design (CRD) with 3 treatments and evaluated by 18 semi-trained panelists as replications. The treatments are: immersion of landrace pork without robusta coffee extract (P0), immersion in 15% robusta coffee extract (P1) and immersion in 35% robusta coffee extract (P2). Organoleptic characteristic variables observed included: appearance, color, aroma, taste, tenderness and overall acceptance of landrace pork. The results showed that the concentration of robusta coffee extract could increase the panelists’ preference for variable aroma, flavor, tenderness, and overall acceptance of landrace pork, compared to control treatment. However, immersion treatment of robusta coffee extract with a concentration of 15% and 35% shows the results of the panelists’ assessment of the same variable appearance (4,7 – 4,8 = normal – rather like) and color of pork (5,1 – 5,0 = quite like – like). The conclusion of the study that landrace pork immersion in robusta coffee extract can improve the organoleptic characteristic of pork in variables of aroma, flavor, tenderness and overall acceptance with the best soaking concentrations is 35% concentration.